Propuesta de señaslización y senderismo para el fomento del turismo del cerro Ahuaca del cantón Calvas provincia de Loja - Castillo Vega, Carmen Paola (2016)
The Cerro Ahuaca is located in the canton Calvas Loja Province, southern Ecuador and is one of the important areas for conservation and water supply to the population of the area , part of the reserve is owned by GAD Bald canton under his administration has retained the existing flora and also within their operational programs can be found reforestation of some areas. The study area has great potential for tourism and ecotourism to become a promising site for tourist activities like camping, hiking,climb,picnic, flora and fauna, among others, for this reason we raised this research work , where you have to know the basic guidelines for the adequacy of signage and definition of the path, with the sole aim of encouraging visitors to tourist activities . This research project revolves around the theme , "Proposed signage and trails to promote tourism of the Canton Bald Hill Ahuaca Loja Province " whose aim is the implementation of a trail and signage, currently subject should be handled in all natural areas such as national parks, forests, hills and protected areas where tourist activities intended to benefit from it. The overall objective of this study is to contribute to a proposal Signaling and Signs for the Promotion of Tourism Ecological Reserve Area Canton Calvas Ahuaca Loja Province , for the development of this target was raised three specific objectives as: Characterize sites canton Ahuaca natural Bald Hill for information of the study area . Analyze the information gathered using the technique of SWOT and Defining an ecological path and signage for Ahuaca hill , which to guide , inform and convey a valuable image of order and quality. Importantly, the methodology used for the development of this study was performed according to the specific objectives presented above , requiring the use of analytic and synthetic methods allowed us to analyze and synthesize a more objective and fast information also obtained and applied inductive and deductive methods important methods which reduce and chose only the information required for representation on a personal level and general historical method that finally helped us gathering all the information of the study area . 7 To characterize the sites under study and assign a hierarchy to the methodology applied by the Ministry of Tourism of Ecuador, which summarized the information in chips, was the description of the attractions, and then proceeded to the hierarchy consisting of individual analysis of each site. To analyze the information collected was used SWOT analysis in which we helped tremendously to get clear about the strengths given weaknesses opportunities and threats that have this attractive . To define the path and signage in place , we used the methodology of Miguel Cifuentes , in order to define what kind of path is required for lifting the route GPS was used to determine the tourism carrying capacity was used Cifuentes methodology was applied to calculate formulas in terms Ahuaca Cerro is physical load capacity , the actual charge capacity , the capacity of handling and effective load so as to possible impacts , resorted to the Leopold matrix cause and effect, the signage is proposed based on study of MINTUR signage Manual , where tones detailed dimensions and materials used. As the results are nested in study sites , reaching Cerro Ahuaca in a hierarchy II , while climbing in the same hierarchy obtained Ahuaca II , we determined the load capacity is 28.62 tourist visits day with regard to the construction of the path it was determined that in certain sectors is indispensable escalerines implementation of wood or stone , as to signage detailed the materials that do not cause environmental impacts . Main conclusions is determined as the reservation is in Ahuaca natural attraction Ahuaca Hill in Canton Bald , is little known , the organizations responsible to disseminate and project the site do not invest the necessary resources for this, besides the names was determined to it is the path I call " tHE TRAIL oF ADVENTURE Ahuaca " with respect to the upper area of the hill I call " tHE VIEWPOINT oF BALD " , names that are institutionalized and that the handle for future studies , the development of this project has been successful thanks to the help and GAD opening the canton representatives who embrace positive bald projects to benefit a new direction to tourism activities within the reserve and also the help of realization and fulfillment of the objectives within the project and contribute to the overall objective of a proposal and Signs signage for the Promotion of Tourism Ecological Reserve Area Canton Calvas Ahuaca Loja province and the specific objectives characterize natural sites Bald Hill Canton Ahuaca for information study area , analyze the information collected through the SWOT technique , define an ecological path and signage for Ahuaca hill , which to guide , inform and transmit valuable and quality image of order Finally, it presents the recommendations are addressed to the authorities such as the Canton GAD Bald , who is in charge or the conservation, protection and dissemination of the aforementioned appeal , to make commitments to implement further trails and signage campaign sensitivity and awareness of conservation of this attractive and generally the entire buffer zone that covers the hill .